2019
DOI: 10.1093/nar/gkz817
|View full text |Cite
|
Sign up to set email alerts
|

Cell-free expression of RNA encoded genes using MS2 replicase

Abstract: RNA replicases catalyse transcription and replication of viral RNA genomes. Of particular interest for in vitro studies are phage replicases due to their small number of host factors required for activity and their ability to initiate replication in the absence of any primers. However, the requirements for template recognition by most phage replicases are still only poorly understood. Here, we show that the active replicase of the archetypical RNA phage MS2 can be produced in a recombinant cell-free expression… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
25
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 11 publications
(28 citation statements)
references
References 71 publications
3
25
0
Order By: Relevance
“…All readout constructs are based on designs by Weise et al (20). For experiments using the PURExpress® In Vitro Protein Synthesis Kit (NEB), standard reactions were supplemented with 10 µM DFHBI-1T, MS2rep and F30-Bro(-) or MS2-Bro(+), respectively, as described for the individual experiments: Fluorescence signals were recorded every 60 s over a total of four hours or every 120 s for six hours for experiments involving F30-Bro(+|-) or MS2-Bro(+|-), respectively.…”
Section: Real Time Uorescence Measurementsmentioning
confidence: 99%
See 3 more Smart Citations
“…All readout constructs are based on designs by Weise et al (20). For experiments using the PURExpress® In Vitro Protein Synthesis Kit (NEB), standard reactions were supplemented with 10 µM DFHBI-1T, MS2rep and F30-Bro(-) or MS2-Bro(+), respectively, as described for the individual experiments: Fluorescence signals were recorded every 60 s over a total of four hours or every 120 s for six hours for experiments involving F30-Bro(+|-) or MS2-Bro(+|-), respectively.…”
Section: Real Time Uorescence Measurementsmentioning
confidence: 99%
“…Next, we sought to explore if the MS2•S1•EF-Ts heterocomplex could be used to initiate transcription of a genuine MS2 template. To this end, we made use of our previously established MS2 RNA polymerase assay for the detection of MS2 replicase activity in recombinant in vitro transcription translation (PURE) systems (20,28). In this assay, a uorescence readout is produced by (+) strand synthesis of the broccoli aptamer from a (-) strand template that is fused with the 3'-end of genomic MS2 (-) strand (F30-Bro(-)), in the presence of the uorogen DFHBI-1T (29) (Fig.…”
Section: Puri Ed Ms2 Replicase Is Functional In Recombinant In Vitro Translation Systemsmentioning
confidence: 99%
See 2 more Smart Citations
“…However, due to its instability and challenging purification [ 96 ], most applications of MS2 phage were focused on RNA-RNA and RNA-protein interactions, such as the RNA imaging mentioned above. A recent study also reported the use of MS2 phage replicase to construct an in-vitro expression system, which provides new ideas for studying the template specificity of MS2 replicase and designing gene circuits with DNA- and RNA-encoded systems [ 98 ]. In addition, there are also reports on the replicases of other types of RNA phages, such as R17 and f2 phage belonging to group I [ 99 , 100 ], GA phage belonging to group II [ 101 ], SP phage belonging to Group IV [ 102 ], and the dsRNA phage ϕ6 belonging to the Cystoviridae family [ 103 ].…”
Section: Rna-based Synthetic Biology Parts From Phage Componentsmentioning
confidence: 99%